2020
DOI: 10.3389/fpsyg.2019.03039
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Sports Participation on Body Image, Self-Efficacy, and Self-Esteem in College Students

Abstract: Objectives: This study aimed to explore the relationship between body image, selfefficacy, self-esteem, and sports participation by gender, grade, and specialty and then to provide a reference for promoting participation in sports and physical activities in college students. Methods: Using stratified random sampling, undergraduate students in western China were selected as participants. The data obtained in this study were processed by SPSS 19.0 and AMOS 21.0 statistical software. Results: Body image was signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
66
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 26 publications
5
66
0
3
Order By: Relevance
“…Because of the constraints of our education system, college students have to spend more time and energy completing schoolwork, which is also one of the factors that reduce physical activity of college students ( Barkley et al, 2019 ). The students with eye use time of 8–10 h in a day have the highest proportion (43.61%), which is the same as the results of Ouyang et al (2020) . As entertainment activities such as computers, mobile phones, tablets, and games take up a lot of time for students, the eye use time is also prolonged greatly.…”
Section: Discussionsupporting
confidence: 81%
“…Because of the constraints of our education system, college students have to spend more time and energy completing schoolwork, which is also one of the factors that reduce physical activity of college students ( Barkley et al, 2019 ). The students with eye use time of 8–10 h in a day have the highest proportion (43.61%), which is the same as the results of Ouyang et al (2020) . As entertainment activities such as computers, mobile phones, tablets, and games take up a lot of time for students, the eye use time is also prolonged greatly.…”
Section: Discussionsupporting
confidence: 81%
“…The sex difference observed in our study may be due to the fact that the effect of physical exercise on overall QoL is better than that of diet control [43]. Boys prefer physical exercise and were more likely to adhere to the intervention measures in the present study, and Yiyi Ouyang et al found that males were more likely to have greater self-efficacy and self-affirmation relative to females, potentially further explaining this sex difference [44]. In addition, there are some prior studies indicating that boys suffer greater QoL impairment than do girls when obese or overweight [45], making it easier to improve the QoL of boys relative to that of girls.…”
Section: Discussionsupporting
confidence: 41%
“…At the same time, boys are better than girls in physical fitness and motor skills, and boys' relative self-discipline weight control efficiency is better than girls, and their sports participation is also better than girls (Hou and Yang, 2017;Hu, 2017). This study also found that seniors were more likely to participate in sports than juniors because they have less academic workload and more disposable time, and the pressure of employment forces them to participate in sports to adjust their body and mind (Ouyang et al, 2020). Therefore, senior students have more advantages in sports participation.…”
Section: Sports Participation In College Studentsmentioning
confidence: 60%